Development of Novel Materials with Photocatalytic Effect - Prof Dr Rakesh Kumar Khandal; Pranshu Chhabra Kapoor; Ruchi Gupta (International Journal of Photochemistry and Photochemical Research, 2024)
For capturing solar energy and for converting it into electric power, it is utmost essential to design materials that can be used for this purpose. Generally, the materials deployed for converting solar energy into electric energy are sensitive to UV-radiation. If the material used for this purpose are sensitive to visible light, it will be the breakthrough research. It has been a challenge to design materials with novelty of being sensitive to visible light. The present paper deals with designing novel materials, sensitive to visible light. For this, UV-sensitive, Titanium dioxide (TiO2) was doped with Cadmium and Tungsten by two different methods. First method involved Ex-situ modification of nanoparticles of the anatase form of titanium dioxide, carried out by doping with cadmium sulphide and tungsten trioxide. Second method involved in-situ simultaneous synthesis of nanoparticles of titanium dioxide and the dopants, using the precursors tetra butyl titanate for titanium dioxide, cadmium chloride for cadmium and sodium tungstate for tungsten. The doped materials were evaluated for characteristics demonstrating their sensitivity to visible light. Results obtained for ex-situ method showed reduction in the band gap energy of TiO2 from 3.2 eV to 2.82 eV and 2.81eV by doping with 1% by wt. of cadmium sulfide and 4% by wt. of tungsten trioxide, respectively, at 400°C. For in-situ method, reduction in band gap energy of TiO2 was observed, from 3.2eV to 2.73eV and 2.81eV with cadmium precursor and tungsten precursor, respectively. In both the cases, doped material exhibited photocatalytic effect in visible light.
Keywords: Band gap; Photocatalytic activity; Titanium Dioxide; ex-situ; in-situ